Analisis Penyebab dan Dampak Kebocoran Bahan Bakar terhadap Keselamatan Operasional Penerbangan - Muhammad Revaldi Pratama Haksu Jeon; Raffy Arrasyfazra Prayogo; Bhima Sakti Araffat; Bambang Sutarmadji (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
International airports are complex work environments with unique occupational health and safety risks. As hubs of intensive transportation activities, airports involve various operations, including flight services, passenger handling, cargo management, and fuel operations. Early detection of fuel leaks is crucial to ensure the aircraft’s fuel system is free from leaks, blockages, or potential fire hazards. This study aims to analyze the causes of fuel leakage and identify appropriate mitigation measures, using observation and literature review methods. The findings indicate that fuel leakage occurring while the aircraft is parked suggests damage to certain fuel system components, such as seal gaskets, sealants, and dome nuts, which may suffer from wear or cracking due to age-related degradation. Such damage poses serious risks, including fire hazards, corrosion to aircraft structures—particularly in hard-to-reach areas like the wings or fuselage—and a drop in fuel pressure that could impair engine performance or cause flight cancellations. To address these issues, thorough inspections of all fuel system components are essential. Additionally, the use of sensors to detect abnormal changes in fuel pressure and flow, combined with rigorous leak testing after repairs, is recommended to ensure operational safety and reliability.